A era Vargas e o teatro: um estudo sobre peças teatrais vetadas entre 1930 e 1945 em São Paulo - Santos Júnior, Valmir Mendes dos (2011)
This Work " The Vargas Era and the theater: a study about plays vetoed between 1930 and 1945 in São Paulo" by Valmir Mendes dos Santos Junior, this text aims to understand govern actions in artistic area, specifically about theater from data of Collection Miroel Silveira of Comunication and Art School of University São Paulo. The First data collected in this collection, enabled to discover 7 plays vetoed between 1930 and 1945, after they were denied by existents organs. This Way, did this research aims to discuss the main social and political aspects presented those plays that were vetoed between 1930 and 1945? For answer of this question, the plays had been studied: "Andaime", "Gaspar o Serralheiro" e "Defesa Passiva" in order to understand the reasons of the mains event lived in the country in that era. The first conclusions of this research indicates that the censure during Vargas govern, became more rigid with the implantation of " New State" (1930-1945). Also highlighting that among the play theme vetoed there were recurrence subjects related to capitalist system criticizen, role of women in the society and also the workers were exploited. Defesa Passiva, specifically mentions officials organs in its plot, and therefore modifications were necessary to suit requirements of the "New State" in order to be aproved its presentation